Neuro-psychological impact on dentists in the COVID-19 pandemic - Soutat Tsolak; Sorana Bucur; Dorin Cocos; Mahmoud Alawawda; Alexandra Ganga; Emilia Rusu; Daniela Manuc (Amaltea Medical Publishing House, 2024)
Our survey investigated dentists' perceptions of their activity during the COVID-19 pandemic. We used a ten-question survey on our conception and sent it to 122 dentists via social media; 70 responded. The Cronbach's Alpha coefficient validated our questionnaire. We applied the Shapiro-Wilk test and the Mann-Whitney test. The chosen p-significance threshold was 0.05. The respondents were 61.50% women and 38.50% men; 44.29% were between 23 -30 years old. 44.29% of the respondents were dentists with 1 to 5 years of practice. Of 70 dentists, 51.43% felt stress, 35.71% felt fear, 7.15% anxiety, and 5.71% physical fatigue during the pandemic. 65% of males and 35% of females used some drugs. 80.80% of respondents had no financial problems, 19.20% reported some troubles. Gloves, masks, and glasses were the principal ways of protection, followed by nebulizers (98%) and UV lamps (52%). 68 declared they had the support of their friends and family, 65 were relaxed by TV programs, 52 by doing sports, and 47 by listening to music. 53% of dentists had COVID-19: 30.58% female and 22.42% male; 96.24% of them managed to treat the infection at home